A rheumatological catastrophe: case of amyopathic juvenile dermatomyositis - Vinod, Meghashree; K., Nikitha (International Journal of Contemporary Pediatrics, 2024)
Juvenile-onset amyopathic dermatomyositis is rare variant of juvenile-onset dermatomyositis (JDM), characterized by the hallmark cutaneous features of dermatomyositis without clinical or laboratory evidence of muscle disease. Dermatomyositis with positive anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody has a distinct phenotype associated with small hand joint arthritis, mucocutaneous ulceration in the absence of muscle involvement. In this article, we describe a 5-year-old child presented with mucocutaneous manifestations with no muscle weakness who responded to immunosuppressive therapy.